(untitled) (Journal of Engineering, 2025)
Traditional concrete has gained several uses in recent decades; yet, it poses some concerns in the building business. The weight of the product is a limitation when it is used in applications that are more specialized. As a result, the building and construction sectors were the ones to introduce the idea of lightweight concrete. In this study, five different pumice lightweight mixtures were utilized (a reference mix that did not include any fiber, a mix that contained 1% glass fiber, a mix that contained one layer of fiber glass mesh, a mix that contained three layers of fiber glass mesh, and a hybrid mix that had both glass fiber and three layers of fiber glass mesh). Every single one of the mixtures that were used underwent tests to determine their compressive strength, center point flexural strength, and splitting tensile strength. Compressive strength, splitting tensile strength, and flexural strength all increased by (20.39%, 138%, and 60.68 %), respectively, as a consequence of the inclusion of fibers into lightweight concrete, according to the findings. There was also a significant improvement in the material’s overall mechanical characteristics.